A study on material-process interaction and optimization for VAT-photopolymerization processes. Issue 9 (12th November 2018) - Aznarte Garcia, Elisa; Qureshi, Ahmed Jawad; Ayranci, Cagri
Abstract : Purpose: This paper aims to present an investigation of material-process interaction of VAT-photopolymerization processes. The aim of the research is to evaluate the effect of different printing factors on the tensile properties, such as elastic modulus, of 3D printed specimens. Design/methodology/approach: To perform this study, Design of Experiments is used by the use of Taguchi's techniques. The relationship between each factor and the elastic modulus, ultimate tensile stress and strain at break is obtained. Furthermore, the total print time is analyzed with respect to the obtained properties. Findings: The study indicates that part orientation, exposure time to the UV light and layer thickness are the most important factors affecting the investigated properties. At the same time, it was found that the highest mechanical properties can be obtained with the shortest printing times. A comprehensive list of factors available on the slicing software and other factors, like the orientation of the part or its position, is investigated. Future studies including post curing and chemical characteristics based on the obtained results are necessary. Originality/value: As a result of this research, it is outlined that using design for additive manufacturing for vat-photopolymerization, especially on DLP processes, 3D printing methods can be stablished. Furthermore, it outlines the possibility of tailoring mechanical properties of printed parts as a function of print parameters and print time. Considering the limited amount of information available in the open literature, the results presented in this paper are of great interest for researchers in the field of VAT-photopolymerization.